Enforcing the Kyoto Protocol : can punitive consequences restore compliance? - Hovi, Jon [et al.] (2007)
Considers whether the use of punitive consequences will induce a country that has violated its Kyoto commitments to return to compliance. Argues that effective deterrence is the best that can be hoped for from a punitive compliance system.